CHIKUNGUNYA FEVER SURVEILLANCE, OUTBREAK INVESTIGATION, RESPONSE AND ITS DETERMINANTS FACTORS IN PESHAWAR, PAKISTAN: A DESCRIPTIVE AND UNMATCHED CASE-CONTROL STUDY - Irshad Roghani; Muhammad Ashfaq; Muhammad Junaid Hassan Sharif; Qasim Khan; Safina Mufti; Noreen Taj (Journal of Ayub Medical College Abbottabad, 2024)
Background: Chikungunya is a viral disease transmitted by Aedes aegypti and Aedes albopictus mosquitoes. It is characterized by fever, joint pain, and rash. The first officially confirmed outbreak in Peshawar, Pakistan, was identified in Shamshatoo Camp, which is an Afghan refugee settlement, in 2024. The objective of this study was to identify the determinants of the outbreak, access the magnitude of the outbreak, and implement control measures. Methods: The study design was a descriptive study followed by an unmatched case-control study (1:1 ratio) conducted between October 10 and November 26, 2024. Data were collected by administering structured questionnaires, active case search, and review of health facility records. In all, 154 cases were recruited and an equal number of controls. Univariate and multivariable logistic regression were computed to determine the relationship between the outcome and associated factors. Mosquito breeding sites were noted in the environmental survey, and later, laboratory testing confirmed 14 positive chikungunya cases out of 43 samples. Results: During the outbreak a total of 416 cases were reported with the peak on November 1, 2024 (32 cases). Females constituted 55% of the total cases and the most affected group belonged to the age group 10–19 years. Other significant risk factors were the presence of mosquito larvae in households (OR 3.2; 95% CI 2.0–5.2), open storage containers for water (OR 3.0; 95% CI 2.0–4.9), and less use of mosquito protection measures (OR 3.4; 95% CI 1.7–6.8). Precaution measures on awareness against vector-borne diseases showed protective effects (OR 0.03; 95% CI 0.01–0.14). Conclusion: The outbreak was driven by inadequate mosquito control, favourable climatic conditions (20–30 °C), and community laxity in eliminating breeding sites. Targeted interventions, including vector control, health education, and distribution of insecticide-treated nets, contributed to the decline in cases. However, the absence of a dedicated health facility and poor health-seeking behaviour remain challenges. Comprehensive surveillance and community engagement are essential to prevent future outbreaks.